Definiowanie mowy nienawiści w orzecznictwie sądów polskich w sprawach karnych - Urbańczyk, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The aim of this article is to answer the question of how hate speech is defined in legal language. The analysis of selected decisions of the Supreme Court, Constitutional Tribunal and common courts issued in criminal cases serves the purpose of the above-mentioned task. In the criminal-law context, it is important to understand such phrases as “public promotion of a fascist or other totalitarian state system”, “public incitement to hatred on the grounds of national, ethnic, racial, religious, or atheistic differences” and “publicly insulting a group of people or an individual because of their national, ethnic, racial, religious, or atheistic affiliation” to define this phenomenon. Based on the above considerations, the manner of understanding and defining the speech of hatred applicable within the legal language will be indicated.
Keywords: hate speech; incitement to hatred; promotion of the totalitarian system; legal language; insulting; Nazi symbols; swastika